Kualitas Layanan, Kualitas Produk, dan Kepercayaan Pelanggan terhadap Keputusan Pembelian Gen Z pada Aplikasi Shopee di Kota Surakarta - Amira, Nura; Radia, Refi Ayu; Tribuana, Nazla Asyifah; Wibisono, Andrea Khoirunnisa; Tamara, Ardelia Putri (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of service quality, product quality, and customer trust on purchasing decisions on the Shopee e-commerce platform. This research uses a quantitative approach with purposive sampling to determine the sample of respondents consisting of Shopee consumers in Surakarta. Data were collected through questionnaires distributed to 150 respondents and analyzed using EViews software to test the hypotheses using multiple linear regression. The results indicate that service quality, product quality, and customer trust have a positive and significant effect on purchasing decisions. Specifically, good service quality, such as quick responses, timely delivery, and effective customer service, has a significant positive impact on purchasing decisions. Additionally, the product quality sold on Shopee, which can be assessed through reviews and ratings, also contributes to the improvement of purchasing decisions. Customer trust in products and the e-commerce platform, particularly regarding product authenticity and transaction security, influences purchasing decisions. The results of the coefficient of determination test show an R-squared value of 0.819692 and an Adjusted R-squared value of 0.814058, meaning that the regression model explains approximately 81.97% of the variation in purchasing decisions. This study contributes significantly to understanding the factors influencing consumer behavior on e-commerce platforms, with a recommendation for future research to consider other variables that may further clarify the factors affecting purchasing decisions.